2019
DOI: 10.3892/ol.2019.10816
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of mRNA expression of CASPs in gastric cancer

Abstract: Current studies suggest that the cysteinyl aspartate specific proteinase (caspase/CASP) family may be closely associated with apoptosis. Scientists have suggested that caspases may be a key to the development of more effective anti-cancer therapies. However, the prognostic value of CASP expression in gastric cancer (GC) remains unclear. Using a Kaplan-Meier plotter online database, the predictive prognostic significance of the expression of 12 CASPs genes (CASP1, CASP2, CASP3, CASP4, CASP5, CASP6, CASP7, CASP8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 57 publications
(57 reference statements)
1
26
0
Order By: Relevance
“…CASP5 is an inflammatory caspase that serves a role in the immune system (27)(28)(29). Inflammation and cancer development are closely associated and a distinct inflammatory environment often exists within tumors (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CASP5 is an inflammatory caspase that serves a role in the immune system (27)(28)(29). Inflammation and cancer development are closely associated and a distinct inflammatory environment often exists within tumors (27).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and cancer development are closely associated and a distinct inflammatory environment often exists within tumors (27). Multiple CASPs are abnormally expressed in GC and associated with the survival rates of GC (28). CASP5 gene overexpression can significantly promote the angiogenesis ability of vascular endothelial cells by promoting the VEGF signaling pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…PAM, CLDN9, CHST6, SLC16A3, KDELR3, and CASP6 are regarded as biomarkers or prognosis genes in the signature, with reports revealing their expression in the areas of the prostate ( Jimenez et al, 2001 ), endometrial lung adenocarcinoma ( Wang Z.H. et al, 2019 ), Uveal Melanoma ( Li et al, 2018 ), and gastric cancer ( Wang Z. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic signi cance of CASP4 overexpression in tumors is controversial. Wang reported that in patients with gastric cancer, higher expression of CASP4 was associated with better OS [17]. However, Terlizzi et al found that CASP4 overexpression is associated with poor prognosis in patients with nonsmall cell lung cancer [18].…”
Section: Discussionmentioning
confidence: 99%